Detergen Cair Ramah Lingkungan Berbasis Metil Ester Sulfonat (MES): STEM Project-Based Learning di SMA Muhammadiyah 9 Kota Bekasi - Nining Nining; Yeni Yeni; Anisa Amalia (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the problems related to the issue of damage to aquatic ecosystems due to environmental pollution in Indonesia is the use of surfactant-based detergents, which make it difficult for people to degrade naturally. Making environmentally friendly liquid detergent products made from MES surfactants can be a learning experience for students using the low-carbon STEM project-based learning model concept. This model is a more practical approach to developing creative thinking skills and is part of a learning community for continuous learning. This service activity is collaborative between universities and schools in applying STEM to chemistry learning. This activity is an alternative form of learning chemistry to stimulate students' fascination and interest in learning material, which is often considered challenging. The activity method uses group simulation and experimental methods to optimize material delivery. Based on evaluation data that was paired t-tested, there was a significant increase in students' understanding of the material (p<0.05) with an increase in the average test score from 40.44 to 89.56. Apart from that, most of the activity participants also showed active participation and enthusiasm.